A Maternal High Fat Diet Has Long‐Lasting Effects on Skeletal Muscle Lipid and PLIN Protein Content in Rat Offspring at Young Adulthood. Issue 2 (1st January 2015) - MacPherson, Rebecca E. K.; Castelli, Laura M.; Miotto, Paula M.; Frendo‐Cumbo, Scott; Milburn, Amanda; Roy, Brian D.; LeBlanc, Paul J.; Ward, Wendy E.; Peters, Sandra J.
Abstract: A maternal high fat diet (HFD) can have adverse effects on skeletal muscle development. Skeletal muscle PLIN proteins (PLIN2, 3 and 5) are thought to play critical roles in lipid metabolism, however effects of HFD on PLIN and lipases (HSL, ATGL, CGI‐58) in mothers as well as their offspring have yet to be investigated. The primary objective of this study was to determine whether maternal HFD would influence skeletal muscle lipase and PLIN protein content in offspring at weaning (19d) and young adulthood (3mo). Female rats (28d old, n = 9/group) were fed control (CON, AIN93G, 7 % soybean oil) or HFD (AIN93G, 20 % lard) for 10 weeks prior to mating and throughout pregnancy and lactation. All offspring were weaned to CON [ n = 18/group, 1 female and 1 male pup per litter were studied at weaning (19d) and 3mo of age]. There was no effect of sex for the main outcomes measured in plantaris, therefore male and female data was combined. Maternal HFD resulted in higher triacylglycerol content in pups at 3mo ( p < 0.05), as well as in the dams ( p = 0.015). Maternal HFD resulted in higher PLIN5 content in pups at weaning and 3mo ( p = 0.05). PLIN2 and PLIN5 content decreased at 3mo versus weaning ( p < 0.001). HFD dams had a higher PLIN3 content ( p = 0.016). Diet had no effect on ATGL, CGI‐58, or HSL content. In conclusion, exposure to a maternal HFD resulted in higher skeletal muscle lipid and PLIN5 content in plantaris of offspring through to young adulthood.